2022
DOI: 10.1093/cid/ciac882
|View full text |Cite
|
Sign up to set email alerts
|

The Geographic Distribution of Dimorphic Mycoses in the United States for the Modern Era

Abstract: Background The dimorphic mycoses (DM) of the United States, Histoplasma, Coccidioides, and Blastomyces, commonly known as endemic mycoses of North America (in addition to Paracoccidioides), are increasingly being diagnosed outside their historical areas of endemicity. Despite this trend, the maps outlining their geographical distributions have not been updated in more than half a century using a large, nationwide database containing individual patient-level data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 22 publications
2
28
0
1
Order By: Relevance
“…A recent analysis of a large dataset of Medicare fee-for-services beneficiaries showed that blastomycosis is being diagnosed more often outside of traditional areas of endemicity [ 22 ]. One possible explanation is the increased use of immunosuppressive therapies, which has led to a recent spike in blastomycosis cases in Quebec [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of a large dataset of Medicare fee-for-services beneficiaries showed that blastomycosis is being diagnosed more often outside of traditional areas of endemicity [ 22 ]. One possible explanation is the increased use of immunosuppressive therapies, which has led to a recent spike in blastomycosis cases in Quebec [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using Occam’s razor’s dictum that the simplest explanation is more likely to be correct, we propose that the SC-WA soil was contaminated via the travel, death and burial of an ancient human or domesticated animal from the central CA region of endemicity to SC-WA. Recent large-scale analyses of clinical cases have established the occurrence of human coccidiomycosis well outside known regions of endemicity ( 9 , 73 ) and, while nearly all such occurrences are likely travel-related, it is possible that other locales contaminated with Coccidioides will be identified. Should those sites be found, the application of the same type of analysis as described here may further shed light on the mechanism by which Coccidioides can spread from its ancestral southwestern sites to colonize other regions.…”
Section: Discussionmentioning
confidence: 99%
“…Due to climate change, the geographic range of endemic mycoses is expanding in the United States, making it likely that increased numbers of cases of infection with these pathogens will be encountered in the future. 31…”
Section: Discussionmentioning
confidence: 99%